Living with Advanced Breast Cancer among Ghanaian Women: Emotional and Psychosocial Experiences. (25th June 2014) - Bonsu, Adwoa Bemah; Aziato, Lydia; Clegg-Lamptey, Joe Nat A.
Abstract : The purpose of this study was to explore the emotional and psychosocial experiences of Ghanaian women living with advanced breast cancer in the Kumasi metropolis. The study employed a qualitative exploratory descriptive design. Purposive sampling approach was used and data was saturated with 10 participants aged between 32 and 65 years. All interviews were audio-taped and transcribed. Data was analyzed concurrently based on the techniques of content analysis. Anonymity and confidentiality were ensured. Women experienced emotional reactions such as sadness, fear, and anxiety. Pain was severe and led to suicidal ideations. Women experienced lost hopes regarding their marriage, parenting, and work. They received support from their families, spouses, colleagues, health professionals, and spiritual leaders. Women coped by accepting the disease and surrendering to God and having the will to live. Five major themes described were emotional reactions, pain, lost hope, support, and coping. It was recommended that health care providers involved in breast cancer management should be trained to enhance effective and holistic care of women and their families. Also, patients with advanced disease should be given effective pain management and a multidisciplinary palliative care team should be instituted to care for the women.